Facilitating Learners’ Self-Regulated Learning Skills and Self-Efficacy to Write in English Using Technologies - Woottipong, Kretsai (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2022)
The purpose of this quasi-experimental research was to study the effects of self-regulated strategy development (SRSD) instruction with explicit generalization training prompted by Constructivist Self-regulating Virtual Composing Activities (CSRVCA) on students’ reported use of self-regulatory strategies, their self-efficacy to write and writing performance. The sample group in this study was 86 high school students who were selected through the use of convenience sampling, then 44 students were assigned to a control group and 42 students were in an experimental group. The students from the experimental group received regular writing classes integrated with constructivist virtual writing instruction, while those from the control group received regular writing classes, required by the school curriculum and syllabus. Instruments included surveys, writing tests, and students’ reflective journals. Data were collected through semi-structured interviews and reflective journals to triangulate quantitative results. The results revealed that the students from the experimental group had a significantly higher level of deploying self-regulatory strategies than those in the control group. They also had a higher level of perceived writing self-efficacy than the students in the control group. Although both groups showed improvement in writing scores, the experimental group outperformed the students in the control group in the post and the delayed post-tests.